2013
DOI: 10.1002/lary.24012
|View full text |Cite
|
Sign up to set email alerts
|

Significance of anterior commissure involvement in early glottic squamous cell carcinoma treated with trans‐oral CO2 laser microsurgery

Abstract: Trans-oral laser surgery is an excellent treatment option in patients with early glottic cancer irrespective of whether or not the AC is involved. Trans-oral laser microsurgery for early glottic cancer involving AC requires adequate exposure, proper assessment, good experience, and advanced surgical skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 33 publications
(46 reference statements)
3
47
3
Order By: Relevance
“…45,46 Tumors involving the anterior commissure generally have a higher risk of local recurrence after TLM, be they Tis, T1a, T1b, or T2. [47][48][49][50][51][52][53][54][55][56] For infiltrating, particularly ulcerating, tumors, the higher recurrence rate is possibly due to deep superior and inferior extensions along the inner perichodrium of the thyroid cartilage, with microscopic spreading to the preepiglottic space and/or to the subglottis but also possibly to microscopic cartilage invasion at this weak spot in the cartilage. 45 Thyroid cartilage resection may be warranted for these tumors.…”
Section: Anterior Commissurementioning
confidence: 99%
“…45,46 Tumors involving the anterior commissure generally have a higher risk of local recurrence after TLM, be they Tis, T1a, T1b, or T2. [47][48][49][50][51][52][53][54][55][56] For infiltrating, particularly ulcerating, tumors, the higher recurrence rate is possibly due to deep superior and inferior extensions along the inner perichodrium of the thyroid cartilage, with microscopic spreading to the preepiglottic space and/or to the subglottis but also possibly to microscopic cartilage invasion at this weak spot in the cartilage. 45 Thyroid cartilage resection may be warranted for these tumors.…”
Section: Anterior Commissurementioning
confidence: 99%
“…In the past, some studies have found it to be a risk factor for recurrent disease [5053], and others have not [29, 5456]. Several recent studies have investigated the anterior commissure as an independent risk factor for local recurrence [43, 5760]. Notably, in a large study from 2009 published by Rödel (463 T1–T2), analysis showed involvement of the AC to be associated with decreased local control in T1a and T1b but not in T2 tumors although survival was not affected.…”
Section: Factors Affecting Oncological Outcomes Of Tlmmentioning
confidence: 99%
“…Our findings are comparable with those of other studies showing an increased incidence of recurrence or residual disease and multiple endoscopic examinations in anterior commissure disease. [17][18][19] We performed transoral laser microsurgery only on two patients with T 1b tumours. This finding reflects our surgeons' concerns about the potential danger of extensive web formation due to the development of opposing wound surfaces, especially in the anterior commissure region.…”
Section: Discussionmentioning
confidence: 99%